Atypical object exploration in infants at-risk for autism during the first year of life - Kaur, Maninderjit; Srinivasan, Sudha M.; Bhat, Anjana N. (Frontiers in Psychology, 2015)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder usually diagnosed after the second year of life. Early signs of ASD within the first year of life are still unclear. The main purpose of the present study was to compare object exploration skills between infants at-risk for ASD and typically developing (TD) infants to determine early markers for autism within the first year of life. Sixteen at-risk infants and 16 TD infants were longitudinally followed from 6 to 15 months of age during an object exploration task involving three objects with distinct size, shape, and texture, i.e., a long rattle, a rigid circular ball, and a soft circular koosh ball. All sessions were videotaped for coding of manual, oral, and visual exploration. We also obtained follow-up outcomes using various developmental questionnaires at 18 months and email follow-up on developmental delays/ASD diagnoses after the infants’ second birthdays. Our results showed object-based differences in exploration patterns that extend across both groups. We also noticed group differences for various object exploration behaviors across objects and ages. Specifically, at 6 months, at-risk infants showed less grasping of the rigid ball as well as less mouthing and greater looking at the rattle compared to TD infants. At 9 and 12 months, at-risk infants demonstrated significantly lower levels of purposeful dropping of all objects. Lastly, at 15 months, at-risk infants looked longer at the rattle and showed persistent mouthing of the rigid ball and rattle compared to TD infants. In addition, 10 out of 16 at-risk infants developed various motor, social, and language delays or ASD diagnoses at follow-up. Taken together, early context-dependent delays/abnormalities in object exploration could be markers for future developmental delays in infants at-risk for autism. Moreover, promoting early object experiences through socially embedded object play could have implications for multisystem development.